Biofouling: Bio‐Inspired Non‐Bactericidal Coating Used for Antibiofouling (Adv. Mater. Technol. 2/2019). Issue 2 (8th February 2019) - Bing, Wei; Tian, Limei; Wang, Yangjun; Jin, Huichao; Ren, Luquan; Dong, Shiyun
Abstract : Inspired by the antifouling properties of the surface of soft coral, Limei Tian and co‐workers describe a graphene‐SE composite material with tentacle structure in article number1800480 . It has an adjusted elastic modulus, originally low surface energy and strong electro‐negativity which benefit to antifouling. Moreover, this elastic material moves harmonically under the stimulus of a fluid medium, rendering the elastic surface unstable, thereby facilitating foul‐release.